An Analysis of Vital Pulmonary Capacity, Haemoglobin Levels and Oxygen Saturation in Conventional Electrical Smokers - Ariyanto, Andhika; Wijayanti, Yuni; Yuniastuti, Ari (Public Health Perspective Journal, 2018)
Smoking habits will accelerate the decline in vital lung capacity, causing an increase in hemoglobin concentration and a decrease of oxygen saturation levels exposed by carbon monoxide. The purpose of this study was to analyze the relationship and differences pulmonary vital capacity, haemoglobin levels and oxygen saturation in conventional electrical smokers. This study used a quantitative approach with analytic observational research and cross sectional design. The research sample was 88 respondents with a simple random sampling technique. Data analysis used chi-square and mann-whitney test. The results showed that there was a relationship between conventional smoker (p= 0,000) and electric smoker (p= 0,000) with vital lung capacity. There was no relationship between hemoglobin level (0.506) and oxygen saturation (p= 0.308) in conventional smoker status. There is no relationship between hemoglobin levels (p= 0.534) and oxygen saturation (p= 0.800) on electric smoker status. There are differences in oxygen saturation levels in conventional smoker status and electric smoker status (p= 0.042). There are no differences in vital lung capacity (p= 0.759) and hemoglobin levels (p= 0.895) conventional smoker status and electric smokers. Citizens who smoke are expected to stop smoking or reduce the number of cigarettes consumsion.